2018
DOI: 10.1083/jcb.201708064
|View full text |Cite
|
Sign up to set email alerts
|

Src-mediated phosphorylation converts FHL1 from tumor suppressor to tumor promoter

Abstract: Wang et al. unveil a new mechanism by which Src may function as an oncogene. Phosphorylation of FHL1 by Src triggers the translocation of FHL1 to the nucleus, where it regulates the activity of the transcription factor BCLAF1 to promote tumor cell growth and loses the ability to regulate cell adhesion and suppress growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Cells were transfected with pCMV-FLAG-FHL1 or pCMV-FLAG using Lipofectamine ® LTX &Plus Reagent (Thermo Fisher Scientific, Inc.). Co-IP was performed as previously described (17), with an anti-FLAG monoclonal antibody (Merck KGaA; cat. no.…”
Section: Co-immunoprecipitation (Ip)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were transfected with pCMV-FLAG-FHL1 or pCMV-FLAG using Lipofectamine ® LTX &Plus Reagent (Thermo Fisher Scientific, Inc.). Co-IP was performed as previously described (17), with an anti-FLAG monoclonal antibody (Merck KGaA; cat. no.…”
Section: Co-immunoprecipitation (Ip)mentioning
confidence: 99%
“…FHL1 overexpression suppresses cell growth through cyclin D1 and E and p27 in head and neck squamous cell carcinoma (16). FHL1 may also be converted from a tumor suppressor to a cell growth accelerator, when FHL1 is phosphorylated by cytosolic tyrosine kinase Src (17). However, its exact role and molecular mechanism in gliomas is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…When oncoprotein Src is overactivated, Src competitively binds with kindlin‐2 to FHL1 and mediates FHL1 phosphorylation. Phosphorylated FHL1 will release the inhibition of wild‐type FHL1 on tumor cells to promote cell proliferation and tumor growth [19]. In addition, knockdown of FHL1 in hepatic carcinoma cells (HCC) significantly increases the sensitivity of HCC cells to paclitaxel, but not to oxaliplatin by enhancing the paclitaxel‐induced activation of caspase‐3 and caspase‐9 [20].…”
mentioning
confidence: 99%
“…FHL1 itself localizes to both focal adhesions and the cell nucleus, and acts as a tumor suppressor by inhibiting cell growth and migration. However, in this issue, reveal that FHL1 can also promote tumor growth when it is phosphorylated by the tyrosine kinase Src (1). …”
mentioning
confidence: 99%
“…Zhang and colleagues, led by Xiang Wang and Xiaofan Wei, focused on protein kinases that mediate integrin-based signaling at focal adhesions and found that the tyrosine kinase Src can bind to FHL1 and phosphorylate the protein on two tyrosine residues, Y149 and Y272 (1). …”
mentioning
confidence: 99%